OFW remittances, community, social and personal services and the growth of social capital - Lopez, Leslie Advincula (2005)
Remittances of Overseas Filipino Workers (OFW) constitute one of the most important
sources of foreign revenues for the Philippines in the last 30 years. While having the
most direct and far-reaching impact on OFW families, remittances seemed to have
failed to create a substantial social development impact both at the national level and
the community-sending localities. These conclusions stem from the observation that
majority of the remittances are spent on consumer durables, dwellings, and education
for their children with only a small percentage of remittances being channeled into
real productive investments. This study argues that OFWs invest in social and personal
services to strengthen their bonds with family and friends, thereby, increasing their
social status/security in the community. Drawing on existing case studies of
communities with known high concentration of overseas workers, the study examines
the social context of OFWs’ spending patterns and shows how these investments
make sense if considered within the structure of their social relations. Utilizing the
concept of social embeddedness and social capital, the study illustrates that seemingly
non-productive investments are actually investments in constructing social capital
(e.g., education support for children/relatives, sponsorships in weddings/baptisms,
medical assistance for relatives) and the social security of their families left behind as
well as when the migrant eventually retires. The results of the study indicate that
remittances do have an important role in the development of social capital both at the
household and community levels through the expansion of the community’s social
and personal services (CSPS).This could enhance the quality of life both at the
individual and community levels but could also exacerbate the heavy burden borne
by overseas workers
Keywords: Overseas Filipino Workers - remittances